Venezuela's humanitarian crisis, resurgence of vector-borne diseases, and implications for spillover in the region. Issue 5 (May 2019) - Grillet, Maria E; Hernández-Villena, Juan V; Llewellyn, Martin S; Paniz-Mondolfi, Alberto E; Tami, Adriana; Vincenti-Gonzalez, Maria F; Marquez, Marilianna; Mogollon-Mendoza, Adriana C; Hernandez-Pereira, Carlos E; Plaza-Morr, Juan D; Blohm, Gabriella; Grijalva, Mario J; et al.
Summary: In the past 5–10 years, Venezuela has faced a severe economic crisis, precipitated by political instability and declining oil revenue. Public health provision has been affected particularly. In this Review, we assess the impact of Venezuela's health-care crisis on vector-borne diseases, and the spillover into neighbouring countries. Between 2000 and 2015, Venezuela witnessed a 359% increase in malaria cases, followed by a 71% increase in 2017 (411 586 cases) compared with 2016 (240 613). Neighbouring countries, such as Brazil, have reported an escalating trend of imported malaria cases from Venezuela, from 1538 in 2014 to 3129 in 2017. In Venezuela, active Chagas disease transmission has been reported, with seroprevalence in children (<10 years), estimated to be as high as 12·5% in one community tested (n=64). Dengue incidence increased by more than four times between 1990 and 2016. The estimated incidence of chikungunya during its epidemic peak is 6975 cases per 100 000 people and that of Zika virus is 2057 cases per 100 000 people. The re-emergence of many vector-borne diseases represents a public health crisis in Venezuela and has the possibility of severely undermining regional disease elimination efforts. National, regional, and global authorities must take action to address these worsening epidemics and prevent their expansion beyond Venezuelan borders.